Severity of Tinnitus Distress Negatively Impacts Quality of Life in Patients With Vestibular Schwannoma and Mimics Primary Tinnitus - Kojima, Takashi; Oishi, Naoki; Nishiyama, Takanori; Ogawa, Kaoru (Frontiers in Neurology, 2019)
ABSTRACT Objective: Quality of life (QoL) and subjective symptoms are predominantly used to evaluate treatment outcome of patients with vestibular schwannoma (VS). However, for patients undergoing conservative treatment—the most frequently used intervention—the association between QoL and subjective symptoms is unclear. Moreover, it is unknown whether VS-related tinnitus could be associated with the audiological and psychological status of the patient. Our overall aim is to provide objective evidence of this association to better guide treatment of VS. Methods: In a prospective study, we analysed factors that influence VS-related tinnitus and QoL in 72 patients receiving conservative management of unilateral sporadic VS. This was done through questionnaires that assessed QoL, anxiety, depression, and audiological examinations. We used the SF-36 Short Form to assess QoL; the Tinnitus Handicap Inventory, Dizziness Handicap Inventory, Facial Clinimetric Evaluation Scale, Visual Analogue Scale for hearing impairment to assess symptoms subjectively; and pure tone audiometry, the speech discrimination for hearing measurements. For psychological status, we used the Hospital Anxiety and Depression Scale. For analyses, we used Pearson correlation analysis and multiple regression between variables and QoL. Results: Correlation and regression analyses revealed that the severity of tinnitus distress had the largest negative impact on QoL in all domains of SF-36. The severity of tinnitus was significantly associated with subjective hearing impairment and the degree of depression and anxiety. Hearing thresholds had no statistical association with severity of tinnitus. Conclusions: To our knowledge, this is the first study to investigate VS-related tinnitus with respect to both patients’ hearing status and psychological condition. Our results suggest that tinnitus distress strongly affects VS patients’ QoL and that its characteristics are similar to primary tinnitus. An intervention for VS-related tinnitus, therefore, should assess to what extent tinnitus bothers patients, and it should reduce any unpleasant emotions that may exacerbate symptoms. This approach should improve their QoL.